Thực hiện các phép tính sau: (-1 + i)(3 + 7i)
Thực hiện các phép tính sau: (-2 - 3i) + (-1 - 7i)
Ta có: (-2 - 3i) + (-1 - 7i) = (-2 - 1) + (-3 - 7)i = -3 - 10i
Thực hiện các phép tính sau:
a) (3-2i)(2-3i)
b) (-1+i)(3+7i)
c) (5(4+3i)
d) (-2-5i)4i
a) Ta có: (3-2i)(2-3i)=(3.2-2.3)+(-3.3-2.2)i=-13i
b) Ta có: (-1+i)(3+7i)=(-1.3-1.7)+(-1.7+1.3)i=-10-4i
c) Ta có: (5(4+3i)=5.4+5.3i=20+15i
d) Ta có: (-2-5i)4i=(-2.0+5.4)+(2.4-5.0)i=20-8i
Thực hiện các phép tính sau: (4 + 3i) - (5 - 7i)
Ta có: (4 + 3i) - (5 - 7i) = (4 - 5) + [3 - (-7)]i = -1 + 10i
Thực hiện các phép tính sau :
a) \(z=\dfrac{\left(1+2i\right)^2-\left(1-i\right)^3}{\left(3+2i\right)^3-\left(2+i\right)^2}\)
b) \(z=\dfrac{-41+63i}{50}-\dfrac{6i+1}{1-7i}\)
Thực hiện các phép tính sau :
a) \(\left(3-2i\right)\left(2-3i\right)\)
b) \(\left(-1+i\right)\left(3+7i\right)\)
c) \(5\left(4+3i\right)\)
d) \(\left(-2-5i\right)4i\)
a) (3 - 2i)(2 - 3i) = (6 - 6) + (-9 -4)i = -13i;
b) (-1 + i)(3 + 7i) = (-3 - 7) + (-7 + 3)i = -10 -4i;
c) 5(4 + 3i) = 20 + 15i;
d) (-2 - 5i).4i = -8i - 20i2 = -8i -20(-1) = 20 - 8i
Thực hiện các phép tính sau: 3+2i+(6+i)(5+i)
3 + 2i + (6 + i)(5 + i)
= 3 + 2i + (6.5 – 1.1) + (6.1 + 5.1).i
= 3 + 2i + 29 + 11i
= 32 + 13i.
Thực hiện các phép tính sau: (3+2i).[(2-i)+(3-2i)]
Thực hiện các phép tính sau: 2i(3+i)(2+4i)
Thực hiện các phép tính sau: 3 + i 2 + i 4 - 3 i 2 - i